An Experimental Survey of Parents' Risk Attitudes Towards Sending Children to Study Abroad - Li, Qian (2009)
This research is conducted to examine Chinese parents’ risk attitudes towards the risks of sending their children abroad. Surveys were distributed among 80 respondents. The target population are blue collars, whose children are still underage. Parents’ self-reported risk preferences are estimated by their importance ratings on a scale of 1-5. Besides, their risk attitudes under hypothetical contexts are elicited from the experiment presented by Holt and Laury (2002). Inconsistencies between the two sets of risk preferences are compared. It was found that most parents are risk seeking for risks coming from physical, psychological and external aspects. In contrast, they are risk averse to the general risks of sending children abroad. There is significant positive relationship between importance ratings and degree of risk aversion for physical, psychological and the combination of three risk types. In all, parents have over-estimated their risk aversion degree to three individual risks: physical, psychological and external. Risk attitudes are also compared between parents with different demographic variables. No significant results can be found between risk aversion and variables such as age, gender, marital status and income. However, parents, who work for the governments, schools and hospitals are more risk seeking than the other occupations. Parents with university qualifications are more risk tolerant than those with lower degrees.